The process of shaping regional policy in Poland - Sługocki, Waldemar (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
The main objective of this piece is to present the process of shaping regional policy in Poland bin the period 1990–2020, with the main focus on theoretical aspects, including the evolution of the paradigm of regional policy in Poland against the background of its changes at the level of the European Union. This text will attempt capturing the impact of Poland’s integration with the European Union on the formulation of domestic regional policy, including the process of drafting new programme documents, both in the national and regional context, as a conscious targeting of pro-development activities in a changing reality, determined by external and internal premises. In order to achieve the outlined research goal, it was necessary to find an answer to the following question: Was the process of shaping regional policy in Poland influenced by Poland’s integration with the European Union and its participation in EU structures? In order to answer the research question formulated like this, the discussion starts with explaining the basic concepts such as: regional development, regional policy, or describing development factors in theories and models of regional development. The following part of the article will outline the process of shaping regional policy in Poland, indicating both theoretical, legal, institutional and financial aspects of the discussed issues.

Zasadniczym celem artykułu jest zaprezentowanie procesu kształtowania polityki regionalnej w Polsce w latach 1990–2020, koncentrując rozważania głównie na aspektach teoretycznych, w tym ewolucji paradygmatu polityki regionalnej w Polsce w kontekście jej zmian na poziomie Unii Europejskiej. W tekście podjęto próbę uchwycenia wpływu integracji Polski z Unią Europejską na formułowanie rodzimej polityki regionalnej, w tym proces tworzenia nowych dokumentów programowych zarówno w wymiarze krajowym, jak i regionalnym jako świadome ukierunkowanie działań prorozwojowych w zmieniającej się rzeczywistości determinowanej przesłankami zewnętrznymi i wewnętrznymi. Aby osiągnąć zakreślone zamierzenie badawcze, konieczne było uzyskanie odpowiedzi na sformułowane pytanie: Czy proces integracji Polski z Unią Europejską oraz uczestnictwo w jej strukturach wpłynęło na kształtowanie polityki regionalnej w Polsce? W celu uzyskania odpowiedzi na tak sformułowane pytanie badawcze rozważania rozpoczęto od wyjaśnienia podstawowych pojęć takich jak: rozwój regionalny, polityka regionalna, czy też opisania czynników rozwoju w teoriach i modelach rozwoju regionalnego. W następnej części artykułu zakreślono proces kształtowania się polityki regionalnej w Polsce, wskazując zarówno aspekt teoretyczny, prawny, instytucjonalny i finansowy omawianych zagadnień.
Proces kształtowania polityki regionalnej w Polsce
Keywords: regional policy; region; development; European Union; polityka regionalna; region; rozwój; Unia Europejska